005 Electroclinical characteristics of autoimmune encephalitis as outcome biomarkers. (29th July 2019) - Wesselingh, Robb; Broadley, James; Kyndt, Chris; Buzzard, Katherine; O'Brien, Terence; Monif, Mastura
Abstract : Introduction: Seizures are a common characteristic of Autoimmune encephalitis (AIE). The use of the electroclinical characteristics to assist in the diagnosis of AIE has been explored 1 however use of specific electroencephalogram (EEG) changes has not been examined with regards to outcome prediction. Methods: Patients with AIE were recruited retrospectively across 4 hospitals in Victoria. Clinical Data was collected during admission and at final follow-up. EEGs of patients were reviewed using an objective proforma. Associations between EEG biomarkers and clinical outcomes were demonstrated using logistic regression modelling. Results: We recruited 88 patients with AIE and available EEGs. Presence of rhythmic delta, superimposed fast activity and an abnormal background were significantly more common in N-methyl-D-aspartame receptor (NMDAR) antibody associated AIE patients (p<0.05). ICU admission was associated with rhythmic delta epileptiform activity (OR 3.25, p=0.046), sharp elements in the EEG abnormality (OR 3.55, p=0.05), and an abnormal background rhythm (OR 3.56, p=0.03). Development of drug resistant epilepsy was associated with prolonged duration of abnormality on EEG (OR 11.99, p=0.013), and sharp elements in the EEG abnormality (OR 7.29, p=0.02). Conclusion: We have identified EEG biomarkers that differentiate NMDAR AIE from other subtypes, and likely represents an objective description of extreme delta brush which has previously been described in NMDAR AIE. 2 We have also demonstrated biomarkers associated with important outcomes that can be used to help guide treatment and prognosis. References: Limotai C, Denlertchaikul C, Saraya AW, Jirasakuldej S. Predictive values and specificity of electroencephalographic findings in autoimmune encephalitis diagnosis. Epilepsy Behav 2018;84:29–36. Veciana M, Becerra JL, Fossas P, Muriana D, Sansa G, Santamarina E, et al. EEG extreme delta brush: An ictal pattern in patients with anti-NMDA receptor encephalitis. Epilepsy Behav 2015;49:280–5.